Programação na televisão pública : uma análise da TV Brasil - Severino, Tiago Nunes (2015)
This research is an analysis of TV Brasil’s schedule. The channel belongs to the Brazil Communications Company (EBC), which began to be broadcasted in December 2007. Its creation is the result of a project by the Ministry of Culture, Communications, the Department of Social Communication of the Presidency and civil society entities. TV Brasil’s scheme counted on debates in the National Forum on Public TV and also in the political field, as the Brazilian Congress. From these aspects, the research seeks to understand how a political project is reflected in a program schedule. The methodological approach requires an understanding of a television program schedule’s formatting mode, according to Jost (2007), Mittel (2004) and Wolton (1996), and also by factors that guide the scheduling of a public TV from observing examples, such as England’s BBC, and Chile’s TVN. Historicizing the time of TV Brasil’s creation allow us to view its project and intentions around its various spheres. With this is possible to observe the schedule with a wider look. It was found that the channel's debut in December 2007 happened abruptly and aimed to give a boost to the conversion into law of the Provisional Measure 398, which created the EBC. In terms of flow, the analysis of schedule shows that TV Brazil is a “geralista” TV station, which practice the “paleotelevisão” model and has a joint programmatic profile, among other aspects, the idea of complementary programs than is broadcasted in the private system and focused, mainly, for social minorities.